Answer:
-1, 2, 6
Explanation:
We have to solve the equation as follows: 1/(x-6) + (x/(x-2)) = (4/(x²-8x+12)).
Now, we have,
![(1)/(x-6) +(x)/(x-2) = (4)/(x^(2)-8x+12 )](https://img.qammunity.org/2020/formulas/mathematics/high-school/h7d9hjvj36wcuwg1bsf0oevpsqyuynmx20.png)
⇒
![((x-2)+x(x-6))/((x-2)(x-6)) = (4)/(x^(2)-8x+12 )](https://img.qammunity.org/2020/formulas/mathematics/high-school/vszw1wlgp7m7txuhhoc7l2py8b1hyd37ru.png)
⇒
![(x-2+x^(2)-6x )/((x-2)(x-6)) =(4)/((x-2)(x-6))](https://img.qammunity.org/2020/formulas/mathematics/high-school/jji14o6lc5vgcouxgc1fmnp9u84ouz1j2w.png)
⇒
![((x-2)(x-6))/(x^(2)-5x-2 )=((x-2)(x-6))/(4)](https://img.qammunity.org/2020/formulas/mathematics/high-school/cvdkzn3ahcjoftqidcoowz3eyu8xwqgcgu.png)
⇒
![(x-2)(x-6)[(1)/(x^(2) -5x-2) -(1)/(4) ]=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/cpqiju5aq9fozexmwqz3291rck2uzdyqqc.png)
⇒
or,
![[(1)/(x^(2) -5x-2) -(1)/(4) ]=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/857iev3ay50hugvt8upo7i72bxvcp9mqgm.png)
If, (x-2)(x-6) =0, then x=2 or x=6
If,
, then
![x^(2) -5x-2=4](https://img.qammunity.org/2020/formulas/mathematics/high-school/h9zpb0wk2gqc7bq0chynre9qp13sib7wdo.png)
and (x-6)(x+1) =0
Therefore, x=6 or -1
So the solutions for x are -1, 2 6. (Answer)